The job demands-resources model: A meta-analytic review of longitudinal studies - Lesener, Tino; Gusy, Burkhard; Wolter, Christine (Work and stress, 2019)
The job demands-resources (JD-R) model is an influential framework to understand how job characteristics foster employee well-being. Differing from the cross-sectional focus of most JD-R model reviews, this meta-analytic review uses longitudinal evidence to validate the essential assumptions within the JD-R model. We highlight two aspects: (1) The assessment of the methodological quality of the available longitudinal studies, and (2) the examination of the essential assumptions - the impact of job characteristics on well-being, and vice-versa - with meta-analytic structural equation modelling (metaSEM). We included 74 studies and evaluated their quality. Eighteen studies suffered from serious methodological shortcomings, whereas 29 studies (39%) were considered high-quality studies. Our meta-analytic structural equation models confirmed the essential assumptions simultaneously. The quality of the studies also had an influence on the goodness-of-fit indices. The models with reciprocal assumptions between job characteristics and well-being fitted the data best. The findings of this meta-analytic review suggest that the JD-R model is an excellent theoretical basis to assess employee well-being for a broad range of organisations. However, more research is needed to clarify the reciprocal relationships between job characteristics and employee well-being, as well as the different influences of challenging and hindering job demands on work engagement.